Target tracking and hardware application for smart wheelchair system for airport passengers with reduced mobility - Ye, Roy Wei Bo (2018)
Leveraging on the advancement of technology, the disability community are enjoying greater privileges which was not made possible prior. Growing demand for assistive technologies are on the rise in disability community as such assistive technologies increase the accessibility available to the disability community. In developing the assistive technologies, need requirements of the disability community are taken into careful consideration to produce a comprehensive aid in providing support without compromising the safety of the disabled. Singapore Changi Airport offers complementary wheelchair services to physically challenged passengers who face difficulties getting around the terminals, the airport personal would personally assist those passengers to their designated destination by manually pushing their wheelchair. This service can be requested from any of the information and customer service counters. However, offering of the said service is labour and capital intensive. The one-to-one service requires considerable amount of manpower and staffs have to undergo trainings to uphold the standard of service as well as handling the safety of the passengers in carrying out the duty. This project aims to design and develop a Smart Wheelchair System that is fully automated with the capability of transporting passengers to their destination without compromising the safety of the disabled. As the Smart Wheelchair System comprises of a broad scope, this report will be focusing on the hardware portion. The designing of the connection used in the hardware to allow the Smart Wheelchair System to function accordingly. The Smart Wheelchair System consists of several hardware, each requiring different voltages to function, hence DC converters are used to convert the power source from the battery into the required amount of power supplies. A circuit board converting the power source will be developed through this project and will be implemented on the Smart Wheelchair System. Controlled laboratory testing will be done to ensure the stability and functionality of the system.